The Influence of Microeconomic-Based Pricing on Marketing Strategy and Consumer Behavior in a Perfectly Competitive Market - Andi; Muammar Rinaldi; Muhammad Aldo (Outline Journal of Economic Studies, 2025)
Pricing is a crucial aspect of microeconomics that has broad implications for marketing strategies and consumer behavior, particularly in a perfectly competitive market structure. This study aims to analyze the influence of microeconomic-based pricing principles on marketing strategies and consumer behavior in a market characterized by multiple sellers, homogeneous products, and transparent pricing information. The research method used is a quantitative approach with multiple linear regression analysis techniques. The sample in this study consisted of 150 respondents, consisting of business actors and consumers in homogeneous goods sectors, such as food commodities and basic necessities. The analysis results show that pricing has a significant effect on marketing strategies and consumer behavior, both partially and simultaneously. Marketing strategy also acts as a mediating variable that strengthens the relationship between price and consumer behavior. The coefficient of determination value of 53.4% indicates that the independent variables in this study are able to explain more than half of the variation in consumer behavior. This finding emphasizes the importance of price as an economic signal in a perfectly competitive market and the need for integration between price efficiency and marketing strategy to maintain a competitive position. This study provides a practical contribution to business actors in formulating pricing policies that are responsive to market dynamics and oriented towards consumer preferences.